Lipid Metabolism Affects Fetal Fraction and Screen Failures in Non-invasive Prenatal Testing - Cao, Jun; Qiao, Longwei; Jin, Jieyu; Zhang, Sheng; Chen, Ping; Tang, Haoyu; Yu, Zheng; Shi, Jingye; Wang, Ting; Liang, Yuting (Frontiers in Medicine, 2022)
Objective: To assess the association between lipid metabolism and fetal fraction, which is a critical factor in ensuring a highly accurate non-invasive prenatal testing (NIPT), and on the rate of screen failures or “no calls” in NIPT. Methods: A total of 4,514 pregnant women at 12–26 weeks of gestation underwent NIPT sequencing and serum lipid measurements. Univariate analysis and multivariate regression models were used to evaluate the associations of serum lipid concentrations with the fetal fraction and the rate of screen failure. Results: The fetal fraction decreased with increased low-density lipoprotein cholesterol and triglyceride (TG) levels, which were significant factors (standardized coefficient: -0.11). Conversely, high-density lipoprotein cholesterol and the interval between the two tests were positively correlated with the fetal fraction. The median fetal fraction was 10.88% (interquartile range, 8.28–13.89%) and this decreased with TG from 11.56% at ≤1.10 mmol/L to 9.51% at >2.30 mmol/L. Meanwhile, multivariate logistic regression analysis revealed that increased TG levels were independently associated with the risk of screen failure. The rate of screen failures showed an increase with TG levels from 1.20% at ≤1.70 mmol/L to 2.41% at >2.30 mmol/L. Conclusions: The fetal fraction and the rate of screen failure in NIPT are affected by TG levels. Meanwhile, in pregnant women with high TG levels, delaying the time between NIPT blood collections can significantly increase the fetal fraction. Keywords: non-invasive prenatal testing; fetal fraction; cell-free DNA; triglyceride; multivariable linear regression models